Effectiveness of Self-Care Promotion Program in Elderly People Undergoing Cataract Surgery, Fang Hospital - Musikathum, Kodchaphorn (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2023)
This study aimed to investigate the effects of a self-care promotion program on elderly individuals who underwent cataract surgery. The experimental group, which received the self-care promotion program, was compared to a control group that received standard care. The sample consisted of individuals aged 60-80 years undergoing cataract surgery for the first time, without surgery-related cataracts. The study comprised two groups, each consisting of 35 patients. The experimental group underwent the self-care promotion program, while the control group received routine care. Data collection tools included a self-care knowledge test, a self-care ability assessment form, and an infection assessment form specific to elderly individuals undergoing cataract surgery. Content validity index (CVI) ranged from 0.98 to 1.0, and confidence values were between 0.85 and 0.90. Data were analyzed using descriptive statistics, the Chi-square test, and Independent t-test. The results revealed that, firstly, infections one week and 28 days after cataract surgery, encompassing symptoms such as eye pain, tearing, and eye discharge, did not significantly differ between the experimental and control groups at the 0.05 significance level. Secondly, post-research comparisons of self-care knowledge and the ability to care for oneself indicated significant differences between the experimental and control groups at the 0.05 significance level, with t-statistic values of 10.55 and 8.14, respectively.